Penerapan Hukum Militer dalam Kasus Desersi Anggota Militer dalam Waktu Damai: Aspek Hukum dan Hak Asasi Individu - Muhammad Ilham Duata; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The application of military law in cases of military personnel desertion during peacetime has significant implications for individual rights. This article analyzes how the application of military law must consider individual rights to maintain a balance between military discipline and protecting individual rights. Article 143 of Law No. 31 of 1997 regulates desertion cases in military law. Implications for individual rights include the right to a fair trial and protection from inhumane punishment. Maintaining this balance requires clear definitions, proper training, proportional law enforcement, as well as transparency and accountability in handling desertion cases.